FORMULATION AND STATISTICAL OPTIMIZATION OF BILAYER SUBLINGUAL TABLETS OF LEVOCETIRIZINE HYDROCHLORIDE AND AMBROXOL HYDROCHLORIDE - Choudhury, Priyanka; Deb, Pulak; Dash, Suvakanta (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of the present study is to formulate and optimize bilayer sublingual tablets of Levocetrizine hydrochloride and Ambroxol hydrochloride using a 23 response surface methodology employing design expert-10.0. Sodium starch glycolate and Camphor were selected as independent variables while disintegration time (sec) and water absorption ratio (%) were considered as responses. Methods: The bilayer sublingual tablets were prepared by direct compression and evaluated for various evaluation parameters including hardness, thickness, friability, drug content uniformity, wetting time, water absorption ratio and disintegration time. The prepared optimized bilayer sublingual tablets of Levocetrizine hydrochloride and Ambroxol hydrochloride having above 2 responses-disintegration time (sec) and water absorption ratio. Results: The optimized batch having concentration of sodium starch glycolate and camphor was found within the standard limit of parametersdisintegration time (sec) and water absorption ratio (%) as 61 sec and 69.67%. Conclusion: The direct compression method in this study is relatively simple and safe and a stable, effective and pleasant tasting bilayer sublingual tablet, which has a good balance over disintegration time and water absorption ratio, was formulated. Keywords: Levocetirizine hydrochloride, Ambroxol hydrochloride, Croscarmellose sodium, Sodium starch glycolate, Camphor, Statistical optimization.